2015
DOI: 10.3168/jds.2014-8519
|View full text |Cite
|
Sign up to set email alerts
|

Administration of probiotics Lactobacillus rhamnosus GG and Lactobacillus gasseri K7 during pregnancy and lactation changes mouse mesenteric lymph nodes and mammary gland microbiota

Abstract: The milk and mammary gland (MG) microbiome can be influenced by several factors, such as mode of delivery, breastfeeding, maternal lifestyle, health status, and diet. An increasing number of studies show a variety of positive effects of consumption of probiotics during pregnancy and breastfeeding on the mother and the newborn. The aim of this study was to investigate the effect of oral administration of probiotics Lactobacillus gasseri K7 (LK7) and Lactobacillus rhamnosus GG (LGG) during pregnancy and lactatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“…There is growing evidence that oral probiotics not only influence the GI tract directly, but also have immunomodulatory effects at distant sites, including the urogenital and respiratory tracts, oral cavity/dentition, mammary gland and skin. Although oral probiotics can prevent and/or decrease frequency or severity of diseases outside of the gastrointestinal tract (i.e., an indirect effect) (Alberda et al, 2007; Lappin et al, 2009; Di Nardo et al, 2014; Esposito et al, 2014; Lee et al, 2015; Zuccotti et al, 2015; Fuchs-Tarlovsky et al, 2016; Gruner et al, 2016; Vieira et al, 2016; Zamani et al, 2016), few studies have directly evaluated the appearance of orally administered probiotic species or changes in host microbial communities at distant sites (De Alberti et al, 2015; Mastromarino et al, 2015; Treven et al, 2015). A recent study in pre-menopausal women demonstrated an increase in orally administered probiotic species in vaginal swabs using qPCR analysis, setting the stage for use of oral probiotics to prevent or treat urogenital infections (Mezzasalma et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence that oral probiotics not only influence the GI tract directly, but also have immunomodulatory effects at distant sites, including the urogenital and respiratory tracts, oral cavity/dentition, mammary gland and skin. Although oral probiotics can prevent and/or decrease frequency or severity of diseases outside of the gastrointestinal tract (i.e., an indirect effect) (Alberda et al, 2007; Lappin et al, 2009; Di Nardo et al, 2014; Esposito et al, 2014; Lee et al, 2015; Zuccotti et al, 2015; Fuchs-Tarlovsky et al, 2016; Gruner et al, 2016; Vieira et al, 2016; Zamani et al, 2016), few studies have directly evaluated the appearance of orally administered probiotic species or changes in host microbial communities at distant sites (De Alberti et al, 2015; Mastromarino et al, 2015; Treven et al, 2015). A recent study in pre-menopausal women demonstrated an increase in orally administered probiotic species in vaginal swabs using qPCR analysis, setting the stage for use of oral probiotics to prevent or treat urogenital infections (Mezzasalma et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A combination of bovine lactoferrin and two probiotics administered to healthy women led to detection of the probiotic species in vaginal swabs, important pilot data for future studies of bacterial vaginosis (De Alberti et al, 2015). Oral probiotics given to mice during pregnancy and lactation modulated the composition of bacterial communities in the mesenteric lymph nodes, mammary gland and milk with implications for neonatal health (Treven et al, 2015). Results were similar in women administered oral probiotics from late pregnancy through lactation showing significant increases in probiotic species in colostrum and milk (Mastromarino et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The milk microbiota has been mostly investigated in women (Hunt et al, 2011;Jost et al, 2013;Fitzstevens et al, 2016) and in cows (Oikonomou et al, 2014;Addis et al, 2016;Falentin et al, 2016); some studies were also conducted in other mammals such as goats, sheep, donkeys, buffalo, water deer, reindeer, or mice (Quigley et al, 2013;McInnis et al, 2015;Treven et al, 2015;Catozzi et al, 2017;Li et al, 2017;Soto Del Rio et al, 2017; Supplementary Table S1). Most studies on milk microbiota have investigated milk collected by manual expression, generally following thorough cleaning of nipples or teats (Oikonomou et al, 2012;Jost et al, 2013;Boix-Amoròs et al, 2016) (Figure 1).…”
Section: Milk Microbiota: Current Studies and Limitsmentioning
confidence: 99%
“…Apart from milk, a limited number of studies have explored the microbiota associated to the bovine teat skin or teat apex (Gill et al, 2006;Braem et al, 2012;Verdier-Metz et al, 2012;Frétin et al, 2018), or the internal teat by sampling foremilk and swabbing the teat canal (Falentin et al, 2016;Derakhshani et al, 2018c). Similarly, only few reports are available about the microbiota associated with the mammary gland tissues in human and mouse (Urbaniak et al, 2014;Treven et al, 2015).…”
Section: Milk Microbiota: Current Studies and Limitsmentioning
confidence: 99%
“…Besides, Lactobacillus have been used in studies of mastitis or colonisation of the mammary gland (MG), as in the Treven et al [71] study, in which L. gasseri K7 and L. rhamnosus GG can modulate the bacterial composition of the mammary gland. These bacteria were selected by the previous demonstration of modulation of MG colonisation capacities and, consequently, colonisation of the infant's gut [72,73].…”
Section: Discussionmentioning
confidence: 99%